TRADISI MAPPASSILI SEBAGAI SALAH SATU PENENTU KEPUASAN KONSUMEN BUGIS PASCA PEMBELIAN PRODUK DI KOTA MAKASSAR - Karim, Kasnaeny; Tajibu, Muhammad Jibril (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
Related to the purchase and consumption of consumptive products (e.g., vehicles, houses, and other luxury goods), Bugis-Makassar society will perform a local tradition called Mappassili, which is a special ceremony performed after purchasing and before consuming the product. This study examines the post-purchase consumer behavior related to local culture. The objective of this study is to analyze the reasons behind the existence of Mappassili tradition and to examine customer satisfaction after implementing this tradition in Bugis-Makassar tribe in Makassar City. This study used a qualitative research method. Data were collected through in-depth interviews with the sample consisted of 20 research informants obtained by applying the snowball sampling technique. The results showed that even though Bugis-Makassar tribe has lived in a modern way of life, they still implement the Mappassili tradition after purchasing the product in order to avoid danger in life or due to the pressure from the parents or families. The Mappassili tradition was not only performed to achieve satisfaction, but also to obtain the feeling of security and comfort in purchasing and consuming the product. Keywords : Bugis-Makassar tribe, Mappassili, post-purchase behavior